Development of market organic waste management through maggot cultivation - Yulianyahya, Raafi Widyaputra; Septiansyah, Salsabila; Fatihah, Siti Nurul; Situmorang, Yohan Elfrido; Ramadan, Ivansya (Pengmasku, 2026)
This community service program aimed to optimize organic waste management at Cikupa Traditional Market, Tangerang Regency, through Black Soldier Fly (BSF) maggot cultivation based on trader empowerment. The program employed participatory methods, including organic waste sorting education, technical assistance for maggot cultivation, and a pilot-scale organic waste processing trial. Quantitative data were collected from 88 market traders through questionnaires and field observations. The results showed that BSF maggot cultivation reduced organic waste volume by 50–80% within 10–14 days. Furthermore, 88% of respondents agreed that maggot cultivation effectively reduced organic waste, 91% perceived additional economic benefits from selling maggots and organic fertilizer, and 84% expressed willingness to participate in sustainable waste sorting programs. These findings indicate that BSF maggot cultivation is an effective, practical, and sustainable community-based approach to organic waste management in traditional market environments.